PENERAPAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA MATA PELAJARAN SEJARAH - Indayati, Candra; Prawardayana, Yoni (Jurnal Analisis Pendidikan Sosial, 2024)
Based on the observation of history learning activities in class X TKR 5 SMK ISLAM 1 KOTA BLITAR, several interesting findings were revealed. First, the students of class X TKR 5 have high interest and motivation in learning. This can be seen from their activeness in answering questions and their enthusiasm for the tasks given by the teacher. Second, the students already have the ability to think critically and think high-level. This can be seen from the results of the work they have done, including problem solving activities (discussions) and information exchange (presentations). However, it turns out that there is one ability that has not been fully developed in this class. That ability is creative thinking. The ability to think creatively is very important in history learning so that students can create new and original ideas. These new and original ideas are useful for them in responding to historical learning materials and phenomena of everyday life that require analysis of thoughts from various perspectives. Therefore, this study aims to improve students' creative thinking skills in history subjects. The learning model used to improve these abilities is Project Based Learning. The data collection technique in this study used observation, while the instrument in this study used the students' creative thinking ability sheet. The results of this study indicate that Project Based Learning is proven to be able to improve students' creative thinking skills in history subjects. This can be seen in the acquisition of the percentage score of creative thinking skills which continues to increase starting from learning cycle I to learning cycle II. The percentage score in the first cycle of learning reached 74% in the "enough" category, while the percentage score in the second cycle of learning reached 84% in the "good" category. Based on this information, there was an increase in students' creative thinking skills by 10%.